Method for producing solids
The method of heating thermosetting compositions above their melting start temperature but below their curing start temperature, followed by cooling and molding, addresses the need for efficient production of complex-shaped solid materials, achieving improved manufacturing outcomes.
Patent Information
- Application Number
- JP2019205513
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-11-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-11-13
AI Technical Summary
There is a demand for new methods to manufacture solid materials from thermosetting compositions, which are used for protecting electrical components, but existing methods lack efficiency in producing solids with complex shapes and thin walls.
A method involving a first heating step where the thermosetting composition is heated above its melting start temperature but below its curing start temperature, followed by a first cooling step where the composition is introduced into a mold and cooled below the melting start temperature, allowing for the formation of solids with complex shapes and improved flowability.
This method enables the production of solids with complex shapes and thin walls, improving the ease of obtaining such forms and enhancing the manufacturing process by maintaining the flowability of the thermosetting composition during cooling.
Smart Images

Figure 0007647014000002 
Figure 0007647014000003 
Figure 0007647014000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a solid of a thermosetting composition. [Background technology]
[0002] Conventionally, electrical components used in vehicles, electrical appliances, etc. have been protected by sealing electronic elements with resins to prevent deterioration caused by dust, moisture, etc. Thermosetting compositions having excellent heat resistance have been widely used for such sealing.
[0003] For example, Patent Document 1 discloses a crystalline thermosetting composition for sealing electric and electronic components, which contains a crystalline radically polymerizable compound, a radical polymerization initiator, etc. Furthermore, Patent Document 1 describes that sealed electric and electronic components can be obtained by various molding methods of thermosetting compositions, and describes in the Examples that the thermosetting composition was cured at a mold temperature of 165°C. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 159387 Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, solid thermosetting compositions have been used up until now for the purpose of protecting electrical components and the like, but in recent years, there has been a demand for new methods for producing such solids.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a new method for producing a solid product of a thermosetting composition. [Means for solving the problem]
[0007] The method for producing a solid material according to the present invention, which has been able to solve the above problems, has the following configuration.
[0008] [1] A method for producing a solid of a thermosetting composition, comprising the steps of: A first heating step of heating at a temperature equal to or higher than the melting initiation temperature (°C) of the thermosetting composition and lower than the curing initiation temperature (°C) of the thermosetting composition; and A method for producing a solid product, comprising a first cooling step of introducing the thermosetting composition into a mold and cooling it to a temperature below the melting initiation temperature (°C).
[0009] As described above, there has been no conventional method for producing a solid product comprising a step of heating a thermosetting composition to a temperature equal to or higher than the melting initiation temperature (°C) and lower than the curing initiation temperature (°C), introducing the composition into a mold, and then cooling the composition. In other words, the present invention can provide a new method for producing a solid product of a thermosetting composition.
[0010] Furthermore, the method for producing a solid material according to the present invention preferably also includes the following configurations [2] to
[13] . [2] The method for producing a solid product according to [1], wherein the thermosetting composition contains a crystalline radically polymerizable compound. [3] The method for producing a solid product according to [2], wherein the thermosetting composition contains a radical generator that generates radicals at a temperature equal to or higher than the curing initiation temperature (°C). [4] The method for producing a solid material according to any one of [1] to [3], wherein the melting initiation temperature is an endothermic initiation temperature TA1 (° C.) in differential scanning calorimetry of the thermosetting composition. [5] The method for producing a solid material according to [4], wherein the endothermic onset temperature TA1 (°C) is 36°C or higher. [6] The method for producing a solid material according to any one of [1] to [5], wherein the curing initiation temperature is a temperature equal to or higher than the endothermic completion temperature TA2 (°C) + 10°C in differential scanning calorimetry of the thermosetting composition. [7] A second heating step of heating the solid material at a temperature equal to or higher than the curing initiation temperature (°C); and The method for producing a solid material according to any one of [1] to [6], further comprising a second cooling step of cooling the solid material to a temperature lower than the curing initiation temperature (° C.). [8] The method for producing a solid material described in [7], in which the heating in the second heating step is performed collectively on multiple solid materials after the first cooling step. [9] The method for producing a solid material described in [7], wherein the heating in the second heating step is carried out by sequentially heating a plurality of the solid materials after the first cooling step.
[10] The method for producing a solid product according to any one of [1] to [9], wherein the thermosetting composition contains a radical scavenger.
[11] The method for producing a solid product according to any one of [1] to
[10] , wherein the thermosetting composition contains a non-crystalline radically polymerizable compound.
[12] The method for producing a solid product according to any one of [1] to
[11] , wherein the crystalline radical polymerizable compound is at least one selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and unsaturated polyester.
[13] The method for producing a solid material according to any one of [1] to
[12] , wherein the solid material is attached to an electrical component when used. Effect of the Invention
[0011] According to the present invention, with the above-mentioned configuration, a new method for producing a solid of a thermosetting composition can be provided. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows a portion of a DSC curve of a thermosetting composition. [Diagram 2] FIG. 2 is a plan view of an assembly of a polybutylene terephthalate container and a glass epoxy substrate. [Diagram 3] FIG. 3 is a cross-sectional view of the assembly of FIG. 2 when placed in a mold. [Figure 4] FIG. 4 is a cross-sectional view of a solid composite. [Diagram 5] FIG. 5 is a plan view of a polybutylene terephthalate frame. [Figure 6] FIG. 6 is a plan view of an assembly of a polybutylene terephthalate container and a glass epoxy substrate. [Figure 7] FIG. 7 is a cross-sectional view of an assembly of a polybutylene terephthalate container, a glass epoxy substrate, and a polybutylene terephthalate frame placed in a mold. [Figure 8] FIG. 8 is a cross-sectional view of a solid composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The method for producing a solid product of the present invention is a method for producing a solid product of a thermosetting composition, and includes a first heating step of heating at a temperature equal to or higher than the melting initiation temperature (°C) of the thermosetting composition and lower than the curing initiation temperature (°C) of the thermosetting composition, and a first cooling step of introducing the thermosetting composition into a mold and cooling it to a temperature lower than the melting initiation temperature (°C).
[0014] As described above, there has been no conventional method for producing a solid product having a step of heating a thermosetting composition at a temperature equal to or higher than the melting start temperature (°C) and lower than the curing start temperature (°C), introducing the composition into a mold, and then cooling the composition. That is, according to the present invention, a new method for producing a solid product of a thermosetting composition can be provided. Furthermore, by introducing the thermosetting composition having flowability after the first heating step into a mold and then cooling the composition, a solid product having a shape that conforms to the shape inside the mold can be obtained. This makes it easier to obtain, for example, a solid product having a complex surface shape or a solid product having a thin wall portion. Below, each step will be described in detail.
[0015] In the first heating step, the thermosetting composition is heated at a temperature equal to or higher than the melting start temperature (°C) of the thermosetting composition and lower than the curing start temperature (°C) of the thermosetting composition. By heating at a temperature equal to or higher than the melting start temperature (°C), the thermosetting composition can be brought into a molten state to exhibit fluidity or improve fluidity. Therefore, the heating temperature is preferably equal to or higher than the melting start temperature (°C) + 10 (°C), more preferably equal to or higher than the melting start temperature (°C) + 15 (°C), and even more preferably equal to or higher than the melting start temperature (°C) + 25 (°C). On the other hand, by heating at a temperature lower than the curing start temperature (°C) of the thermosetting composition, it is possible to prevent a decrease in the fluidity of the thermosetting composition. Therefore, the heating temperature is preferably equal to or lower than the curing start temperature (°C) - 5 (°C), more preferably equal to or lower than the curing start temperature (°C) - 10 (°C), and even more preferably equal to or lower than the curing start temperature (°C) - 20 (°C).
[0016] The melting start temperature (°C) of the thermosetting composition is the temperature (°C) at which the thermosetting composition starts to melt. The melting start temperature (°C) can be the endothermic start temperature TA1 (°C) in differential scanning calorimetry (DSC) of the thermosetting composition. The endothermic start temperature TA1 (°C) corresponds to the temperature at point A1 where the heat flow (mW) starts to decrease away from the baseline B1 toward the endothermic peak P in a DSC curve as shown in FIG. 1 obtained by heating the thermosetting composition from -60°C to 200°C at a heating rate of 10°C / min. The vertical axis of the DSC curve indicates the heat flow (mW), and the horizontal axis indicates the temperature (°C). In the case of a thermosetting composition in which no endothermic peak is observed in the DSC curve, the heating temperature in the first heating step may be, for example, 36°C or higher. The heating temperature is more preferably 40°C or higher, even more preferably 50°C or higher, even more preferably 60°C or higher, and particularly preferably 70°C or higher.
[0017] The curing initiation temperature (°C) of a thermosetting composition is the temperature (°C) at which the thermosetting composition begins to cure. The curing initiation temperature (°C) corresponds to the temperature at which the heat flow (mW) starts to increase away from the low-temperature baseline toward the exothermic peak in a DSC curve obtained by heating the thermosetting composition from -60°C to 200°C at a heating rate of 10°C / min. The exothermic peak is a peak that appears on the higher temperature side than the endothermic peak.
[0018] In the first cooling step, the thermosetting composition is introduced into a mold and cooled to a temperature below the melting start temperature (°C). As described above, by introducing the thermosetting composition having fluidity after the first heating step into a mold and then cooling it, a solid body having a shape that conforms to the shape inside the mold can be obtained. In the first cooling step, it is preferable to cool to a temperature of melting start temperature (°C) -10°C or less, more preferably to a temperature of melting start temperature (°C) -20°C or less, and even more preferably to a temperature of melting start temperature (°C) -25°C or less. Specifically, it is preferable to cool to a temperature of 45°C or less, more preferably to a temperature of 35°C or less, and even more preferably to a temperature of 30°C or less. This makes it easier to release the solid body from the mold without destroying its shape.
[0019] The temperature of the mold before the introduction of the thermosetting composition in the first cooling step is preferably 5°C or higher. This makes it easier to maintain the fluidity of the thermosetting composition to a certain extent, making it easier to obtain a solid product having a shape that matches the shape inside the mold. The temperature is more preferably 15°C or higher, and even more preferably 20°C or higher. On the other hand, the upper limit of the temperature is not particularly limited, but may be, for example, 35°C or lower.
[0020] "Inside the mold" means the inside of a mold having a certain shape, and examples of the material include the inside of a container for molding, the inside of a metal mold, gaps present in an electronic component, the inside of a recess present on the surface of an electronic component, etc. The material of the mold is not particularly limited, but examples include metal, resin, etc., and heat-resistant materials are preferable.
[0021] The method of introducing the thermosetting composition into the mold is not particularly limited, and examples thereof include a method of injecting the thermosetting composition into the mold, a method of dropping the thermosetting composition into the mold, a method of injecting the thermosetting composition into the mold, and a method of pushing the thermosetting composition into the mold. Specific examples thereof include an injection molding method, a transfer molding method, an insert molding method, a compression molding method, and a hot melt molding method. The pressure when introducing the thermosetting composition into the mold is, for example, preferably 0.1 MPa or more, more preferably 0.3 MPa or more, even more preferably 1 MPa or more, and even more preferably 2 MPa or more. On the other hand, the pressure is preferably 10 MPa or less, and more preferably 5 MPa or less.
[0022] The solid is a thermosetting composition introduced into a mold and given a certain shape. The solid is not limited to a solid having a certain shape when released from the mold, but may have a certain shape in the mold. The solid can be used for, for example, adhesion, fixing, sealing, etc. For example, the solid may be adhered to the mold, or may be adhered to a member other than the mold (hereinafter, may be referred to as other member). The solid may be adhered or fused to the mold and other member to adhere or fix them together. The solid may seal the mold, seal other members, or seal the mold and other members. Examples of other members include electronic components, resin plates, metal plates, resin rods, and metal rods. The shape of the solid is not particularly limited, but may be a sheet, a polygonal column, a cylinder, a rectangular parallelepiped, a rectangular parallelepiped, a cone, a pyramid, a sphere, etc.
[0023] The method for producing a solid product preferably further includes a second heating step of heating the solid product to a temperature equal to or higher than the curing start temperature (°C), and a second cooling step of cooling the solid product to a temperature lower than the curing start temperature (°C). By carrying out a curing process on a solid product having a shape that conforms to the shape inside the mold in this way, a cured solid product having a desired shape can be easily obtained. Furthermore, by carrying out the curing process, heat resistance is improved.
[0024] The heating temperature in the second heating step is more preferably at least the curing start temperature (°C) + 10 (°C), even more preferably at least the curing start temperature (°C) + 30 (°C), and even more preferably at least the curing start temperature (°C) + 40 (°C). On the other hand, the manufacturing cost can be reduced by setting the heating temperature at no more than the curing start temperature (°C) + 100 (°C). Therefore, the heating temperature is preferably at no more than the curing start temperature (°C) + 100 (°C), more preferably at no more than the curing start temperature (°C) + 80 (°C), even more preferably at no more than the curing start temperature (°C) + 70 (°C), and even more preferably at no more than the curing start temperature (°C) + 60 (°C).
[0025] The heating time in the second heating step is preferably 1 minute or more, more preferably 2 minutes or more, and preferably 250 minutes or less, more preferably 100 minutes or less, even more preferably 30 minutes or less, and even more preferably 10 minutes or less.
[0026] The second heating step may be performed after the first cooling step while the solid of the thermosetting composition is still in the mold. This eliminates the need to remove the solid, improving workability. On the other hand, the second heating step may be performed after the solid of the thermosetting composition is released from the mold after the first cooling step and removed from the mold. The second heating step may also be performed after the solid of the thermosetting composition is released from the mold after the first cooling step and removed from the mold, and the removed solid is placed in another mold before the second heating step. The other mold is preferably smaller in volume than the mold used in the first cooling step. It is also preferable that the other mold has a smaller mass (g) than the mold used in the first cooling step. This makes it easier for heat to be transferred to the solid, and therefore makes it easier for the solid to harden. The material of the other mold is not particularly limited, but examples include metal, resin, and the like.
[0027] The heating in the second heating step may be performed collectively on the plurality of solids after the first cooling step. For example, the plurality of solids after the first cooling step may be placed in a heating furnace and heated collectively. By heating collectively in this manner, workability is improved.
[0028] The heating in the second heating step may be performed by sequentially heating the solid materials after the first cooling step. For example, the solid materials after the first cooling step may be placed on a conveyor and heated by passing them through a continuous heating furnace. This reduces the variation in hardness of the hardened solid materials.
[0029] In the second cooling step, it is preferable to cool to a temperature below the hardening initiation temperature (°C), it is more preferable to cool to a temperature below the melting initiation temperature (°C), it is even more preferable to cool to a temperature below the melting initiation temperature (°C) -10°C, and it is even more preferable to cool to a temperature below the melting initiation temperature (°C) -25°C.
[0030] The thermosetting composition may be any composition that can be hardened by heat treatment.
[0031] The endothermic onset temperature TA1 (°C) of the thermosetting composition is preferably 36°C or higher. This makes it easier to improve the blocking resistance of the obtained solid material. It is more preferably 40°C or higher, and even more preferably 50°C or higher. On the other hand, the endothermic onset temperature TA1 (°C) of the thermosetting composition is preferably 70°C or lower. This makes it easier to bring the thermosetting composition into a molten state, thereby reducing production costs. It is more preferably 60°C or lower, and even more preferably 55°C or lower.
[0032] The curing start temperature of the thermosetting composition is preferably a temperature equal to or higher than the endothermic completion temperature TA2 (°C) + 10°C in the differential scanning calorimetry of the thermosetting composition. This makes it easier to prevent the curing of the thermosetting composition in the first heating step. The curing start temperature is more preferably equal to or higher than the endothermic completion temperature TA2 (°C) + 15°C, and even more preferably equal to or higher than the endothermic completion temperature TA2 (°C) + 20°C. The endothermic completion temperature TA2 (°C) can be measured using a differential scanning calorimeter in the same manner as the endothermic start temperature TA1 (°C), and corresponds to the temperature at point A2 where the heat flow (mW) increases from the endothermic peak P and reaches the baseline B2 in the DSC curve as shown in FIG. 1. The curing start temperature of the thermosetting composition can be controlled, for example, by adjusting the type and amount of the polymerizable compound and the radical generator described later. The endothermic completion temperature TA2 (°C) of the thermosetting composition is preferably 60°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher. On the other hand, the endothermic completion temperature TA2 (°C) of the thermosetting composition is preferably 80°C or lower, more preferably 78°C or lower, and further preferably 76°C or lower.
[0033] The thermosetting composition preferably contains a radical polymerizable compound, and more preferably contains a crystalline radical polymerizable compound. The thermosetting composition contains a crystalline radical polymerizable compound, which can easily improve the residence stability, blocking resistance, curability (curing time), etc., described below. The radical polymerizable compound can be one having a radically polymerizable carbon-carbon double bond. The radical polymerizable compound is not limited to one, but may have two or more, or may have three or more radically polymerizable carbon-carbon double bonds. The crystalline radical polymerizable compound is excellent in flowability in the first heating step and curability in the second heating step. The term "crystallinity" means that an endothermic peak is observed in a DSC curve obtained by heating the composition from -60°C to 200°C at a heating rate of 10°C / min in differential scanning calorimetry. As the crystalline radical polymerizable compound, at least one selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, unsaturated polyester, and crystalline radical polymerizable monomer is preferred, and at least one selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and unsaturated polyester is more preferred. Note that "(meth)acrylate" means "acrylate" or "methacrylate".
[0034] Examples of epoxy (meth)acrylates include epoxy (meth)acrylates obtained by addition reaction of acrylate or methacrylate with epoxy resin having two or more glycidyl ether groups in one molecule, and having a double bond derived from acrylate or methacrylate at the molecular end.Specific examples include (meth)acrylate adducts of bisphenol A type epoxy resins, (meth)acrylate adducts of hydrogenated bisphenol A type epoxy resins, (meth)acrylate adducts of phenol or cresol novolac type epoxy resins, and (meth)acrylate adducts of biphenyl type epoxy resins.These can be used alone or in combination of two or more.
[0035] Examples of the urethane (meth)acrylate include compounds obtained by reacting at least two or more compounds selected from the group consisting of polyisocyanate, hydroxyl group-containing (meth)acrylate, and polyol.
[0036] Examples of polyisocyanates include aromatic polyisocyanate compounds and aliphatic polyisocyanate compounds. Specific examples include tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, trifunctional isocyanate having an isocyanurate ring obtained by trimerizing a bifunctional isocyanate compound, and isocyanate prepolymer modified with a polyol. These can be used alone or in combination of two or more kinds.
[0037] Examples of hydroxyl group-containing (meth)acrylates include hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, phenoxyhydroxypropyl (meth)acrylate, trimethylolpropane di(meth)acrylate, dipropylene glycol mono(meth)acrylate, etc. These can be used alone or in combination of two or more.
[0038] Examples of polyols include polyalcohols having two or more hydroxyl groups in one molecule, polyester polyols having two or more hydroxyl groups in one molecule, polyether polyols having two or more hydroxyl groups in one molecule, etc. These can be used alone or in combination of two or more kinds.
[0039] Examples of polyalcohols having two or more hydroxyl groups in one molecule include neopentyl glycol, ethylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, propylene glycol, diethylene glycol, dipropylene glycol, trimethylene glycol, hydrogenated bisphenol A, bisphenol A ethylene oxide adduct, and bisphenol A propylene oxide adduct. Examples of polyester polyols having two or more hydroxyl groups in one molecule include saturated polyester polyols obtained by dehydration condensation reaction of polyalcohols such as neopentyl glycol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, trimethylene glycol, hydrogenated bisphenol A, ethylene oxide adduct of bisphenol A, and propylene oxide adduct of bisphenol A with polybasic acids such as adipic acid, (anhydrous) phthalic acid, isophthalic acid, terephthalic acid, and trimellitic acid. Examples of polyether polyols having two or more hydroxyl groups in one molecule include polyethylene glycol, polypropylene glycol, and polycaprolactone. These can be used alone or in combination of two or more.
[0040] Examples of polyester (meth)acrylates include polyester (meth)acrylates obtained by esterification of polyester polyol with (meth)acrylate, polyester (meth)acrylates having a (meth)acrylate double bond at the molecular end obtained by reaction of an acid-terminated polyester with a (meth)acrylate having a glycidyl group, etc. These can be used alone or in combination of two or more kinds.
[0041] Examples of polyether (meth)acrylates include polyether (meth)acrylates obtained by esterification of polyether polyol with (meth)acrylate, and polyether (meth)acrylates having a (meth)acrylate double bond at the molecular end obtained by reaction of an acid-terminated polyether with a (meth)acrylate having a glycidyl group, etc. These can be used alone or in combination of two or more kinds.
[0042] Examples of unsaturated polyesters include those synthesized by dehydration condensation reaction of unsaturated polybasic acids, saturated polybasic acids, and glycols. Examples of unsaturated polybasic acids include maleic acid, maleic anhydride, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, glutaconic acid, etc. Examples of saturated polybasic acids include phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, HET acid, and tetrabromophthalic anhydride, etc. Examples of glycols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butanediol, hydrogenated bisphenol A, bisphenol A propylene oxide compound, cyclohexanedimethanol, dibromineopentyl glycol, etc. These can be used alone or in combination of two or more.
[0043] Examples of the crystalline radical polymerizable monomer include ethoxylated isocyanuric acid triacrylate, polyethylene glycol di(meth)acrylate, methoxypolyethylene glycol (meth)acrylate, behenyl acrylate, tetramethyl piperidyl methacrylate, trimethallyl isocyanurate, diacetone acrylamide, itaconic acid dimethyl ester, vinyl stearate, N-vinyl carbazole, N-methylolacrylamide, acrylamide, tolylenediallyl carbamate, maleimide, acenaphthylene, etc. These can be used alone or in combination of two or more kinds.
[0044] These radically polymerizable compounds can be made crystalline by adjusting the combination and blending ratio of each component.
[0045] In 100% by mass of the thermosetting composition, the content of the crystalline radical polymerizable compound is preferably 5% by mass or more, more preferably 10% by mass or more. This makes it easier to cure during the curing process. On the other hand, the content of the crystalline radical polymerizable compound is preferably 90% by mass or less, more preferably 50% by mass or less, and even more preferably 25% by mass or less. This makes it easier to add various additives and have them exert their respective functions.
[0046] The thermosetting composition may contain a non-crystalline radical polymerizable compound. The term "non-crystalline" means that no endothermic peak is observed in a DSC curve obtained by heating the composition from -60°C to 200°C at a heating rate of 10°C / min in differential scanning calorimetry. The non-crystalline radical polymerizable compound can be made to have non-crystalline properties by adjusting the combination and blending ratio of each component of the radical polymerizable compound.
[0047] In 100% by mass of the thermosetting composition, the content of the non-crystalline radically polymerizable compound is preferably 2.5% by mass or more, more preferably 5% by mass or more, and is preferably 45% by mass or less, more preferably 25% by mass or less, and even more preferably 13% by mass or less.
[0048] The thermosetting composition may contain a radical polymerizable monomer that is liquid at room temperature. Examples of the radical polymerizable monomer that is liquid at room temperature include acrylates; methacrylates; vinyl aromatic compounds such as styrene monomers having a vinyl group, α-methylstyrene, vinyl toluene, and α-chlorostyrene; vinyl esters such as vinyl acetate, vinyl propionate, vinyl lactate, and vinyl butyrate; and (meth)acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, and n-butyl methacrylate. These can be used alone or in combination of two or more kinds. The preferred content of the radical polymerizable monomer that is liquid at room temperature can be referred to the description of the preferred content of the non-crystalline radical polymerizable compound.
[0049] The thermosetting composition may contain a radically polymerizable monomer having two or more functionalities, such as triallyl cyanurate, diethylene glycol dimethacrylate, diallyl tetrabromophthalate, phenoxyethyl acrylate, 2-hydroxyethyl acrylate, 1,6-hexanediol diacrylate, diallyl phthalate having an allyl group, diallyl maleate, diallyl fumarate, triallyl isocyanurate, etc. These may be used alone or in combination of two or more kinds.
[0050] The thermosetting composition may contain a radical polymerizable polymer such as a diallyl phthalate prepolymer, a tyrenic prepolymer, an epoxy prepolymer, a urethane prepolymer, an acrylate prepolymer, etc. These may be used alone or in combination of two or more kinds.
[0051] The thermosetting composition may contain a thermosetting resin. Examples of the thermosetting resin include epoxy resin, cyanate ester resin, unsaturated polyester resin, vinyl ester resin, phenol resin, urea-melamine resin, polyimide, and bismaleimide resin. These may be used alone or in combination of two or more. In 100% by mass of the thermosetting composition, the content of the thermosetting resin is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 90% by mass or less, more preferably 50% by mass or less, and even more preferably 25% by mass or less.
[0052] The thermosetting composition preferably contains a radical generator that generates radicals at a temperature equal to or higher than the curing initiation temperature (°C). Examples of the radical generator include thermally decomposable organic peroxides. The radical generating temperature TB1 (°C) of the radical generator is preferably 90°C or higher, more preferably 100°C or higher, and even more preferably 105°C or higher, and is preferably 170°C or lower, more preferably 150°C or lower, and even more preferably 130°C or lower. In 100% by mass of the thermosetting composition, the content of the radical generator is preferably 5% by mass or lower, more preferably 2% by mass or lower, and even more preferably 1% by mass or lower. On the other hand, the lower limit may be, for example, 0.05% by mass or higher.
[0053] Examples of organic peroxides include t-butylperoxy-2-ethylhexyl monocarbonate, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, t-butyl peroxyoctoate, benzoyl peroxide, methyl ethyl ketone peroxide, acetylacetone peroxide, t-butyl peroxybenzoate, dicumyl peroxide, etc. These may be used alone or in combination of two or more.
[0054] The thermosetting composition preferably contains a radical scavenger. Examples of the radical scavenger include quinones such as hydroquinone, monomethyl ether hydroquinone, toluhydroquinone, di-t-4-methylphenol, monomethyl ether hydroquinone, phenothiazine, t-butylcatechol, parabenzoquinone, and pyrogallol, 2,6-di-t-butyl-p-cresol, 2,2-methylene-bis-(4-methyl-6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenol), and 1,2,3-tris-(2-methyl-4-hydroxy-5-t-butylphenol). Examples of the compound include phenol compounds such as 2,2,6,6-tetramethylpiperidine-1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-carboxy-2,2,6,6-tetramethylpiperidine-1-oxyl, and 2,2,6,6-tetramethylpiperidine-1-oxyl. By using these, it is possible to suppress the increase in viscosity during melting. These may be used alone or in combination of two or more. In 100% by mass of the thermosetting composition, the content of the radical scavenger is preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less. The lower limit may be, for example, 0.01% by mass or more.
[0055] The thermosetting composition may contain a filler for improving strength, etc. Examples of the filler include inorganic fillers. Examples of the inorganic filler include calcium carbonate, magnesium carbonate, barium carbonate, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, magnesium oxide, alumina, silica, zinc oxide, mica, aluminum nitride, and boron nitride. Among these, silica is preferred because it is easy to flow. These may be used alone, or two or more may be used in combination. In 100% by mass of the thermosetting composition, the content of the filler is preferably 50% by mass or more, and more preferably 70% by mass or more. This makes it easier for the filler to exert its function. On the other hand, the content of the filler is preferably 95% by mass or less, and more preferably 90% by mass or less.
[0056] The thermosetting composition may further contain various additives. Examples of additives include coupling agents, flame retardants, weathering agents, light resistance agents, colorants, stress relaxation agents, release agents, and curing accelerators. These may be used alone or in combination of two or more. In 100% by mass of the thermosetting composition, the total content of various additives is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. The lower limit may be, for example, 0.01% by mass or more, or 0.1% by mass or more.
[0057] Examples of the coupling agent include silane coupling agents and titanate coupling agents. Examples of the silane coupling agent include epoxy silanes, amino silanes, cationic silanes, vinyl silanes, acrylic silanes, mercapto silanes, and composites thereof. These may be used alone or in combination of two or more. Examples of the flame retardant include halogen-based, phosphorus-based, nitrogen-based, and composite organic flame retardants; inorganic flame retardants such as metal hydroxides, antimony-based, red phosphorus-based, silicone-based, and borate salts. These may be used alone or in combination of two or more. Examples of the weathering agent include antioxidants such as phenols, and ultraviolet absorbing agents such as benzophenone compounds. Examples of the light-resistant agent include benzophenone compounds, salicylate compounds, benzotriazole compounds, and hindered amine compounds. Examples of the colorant include pigments and dyes. Examples of pigments include kaolin, synthetic iron oxide red, cadmium yellow, nickel titanium yellow, strontium yellow, hydrous chromium oxide, chromium oxide, cobalt aluminate, and synthetic ultramarine blue. Examples of dyes include isoindolinone, isoindoline, quinophthalone, xanthene, diketopyrrolopyrrole, perylene, perinone, anthraquinone, indigoid, oxazine, quinacridone, benzimidazolone, violanthrone, phthalocyanine, and azomethine. These may be used alone or in combination of two or more. Examples of stress relaxation agents include silicone oil, silicone rubber, acrylic rubber, urethane rubber, acrylonitrile-butadiene rubber, and thermoplastic elastomer. Examples of release agents include waxes such as fatty acid-based, fatty acid metal salt-based, and mineral-based waxes.
[0058] Examples of the curing accelerator include modified imidazole curing accelerators, modified aliphatic polyamine accelerators, and modified polyamine accelerators.
[0059] The thermosetting composition preferably has a melt viscosity of 1000 Pa·s or less at 90°C. This makes it easier to mold the thermosetting composition to the shape inside the mold. It is more preferably 200 Pa·s or less, even more preferably 100 Pa·s or less, and even more preferably 30 Pa·s or less. On the other hand, the lower limit of the melt viscosity of the thermosetting composition may be 0.5 Pa·s or more, or may be 1 Pa·s or more. The melt viscosity can be measured by the method described in the Examples below.
[0060] The thermosetting composition preferably has a melt viscosity change rate of less than 10% before and after heating at 90°C for 24 hours, more preferably less than 5%, and even more preferably 3% or less. This can improve the retention stability of the thermosetting composition. On the other hand, the lower limit of the melt viscosity change rate may be, for example, 0.5% or more. The melt viscosity change rate can be measured by the method described in the Examples below.
[0061] The thermosetting composition preferably has a curing time of 300 minutes or less when heated at 165°C, as measured based on the method described in the Examples below. This improves workability. The curing time is more preferably 200 minutes or less, even more preferably 50 minutes or less, even more preferably 5 minutes or less, and particularly preferably 3 minutes or less. On the other hand, the lower limit of the curing time may be 1 minute or more, or may be 2 minutes or more.
[0062] The thermosetting composition preferably has a weight loss rate of less than 1%, more preferably less than 0.5%, and even more preferably less than 0.3% before and after heating at 200°C for 1 hour. This improves heat resistance. On the other hand, the lower limit of the weight loss rate may be, for example, 0.1% or more. The weight loss rate can be measured by the method described in the Examples below.
[0063] The thermosetting composition preferably has a glass transition point of 0° C. or higher, more preferably 50° C. or higher, and even more preferably 110° C. or higher. On the other hand, the thermosetting composition may have a glass transition point of 300° C. or lower, or may have a glass transition point of 260° C. or lower. The glass transition point can be measured by the method described in the Examples below.
[0064] The solid material is preferably used by being attached to an electric component. Examples of the electric component include an inverter, a power module, an ignition coil, an engine control unit (ECU), and a sensor such as an oil level sensor. The solid material may be attached to the surface of the electric component, may be attached to the inside of the electric component, or may be attached to both the surface and the inside of the electric component. The same applies to the hardened solid material.
[0065] The manner in which the solid material adheres to the electrical component includes a manner in which the solid material seals at least a part of the electrical component, a manner in which the solid material is bonded to at least a part of the electrical component, a manner in which the solid material is fixed to at least a part of the electrical component, etc. Examples of the at least a part of the electrical component include a gap present in the electronic component, a recess present on the surface of the electronic component, an electronic substrate provided in the electronic component, an electronic element provided in the electronic component, etc.
[0066] The method of attaching the solid to the electric component is not particularly limited. For example, the solid can be attached to the electric component by contacting the molten thermosetting composition with the electric component during the first heating step and the first cooling step, and then cooling. This makes it easier for the solid to conform to the shape of the electric component, improving the adhesion of the solid to the electric component. Alternatively, a solid may be formed in a mold other than the electric component during the first heating step and the first cooling step, and the solid may be released and removed, and the solid may be brought into contact with the electric component during the second heating step and then cooled to attach the solid to the electric component. Alternatively, the cured solid obtained after the second heating step may be attached to the electric component using an adhesive or the like. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified within the scope of the above and below mentioned aims, and all such modifications are included in the technical scope of the present invention.
[0068] <Method for producing thermosetting composition> The following ingredients were mixed uniformly in the amounts shown in Table 1 using a twin-screw kneading extruder adjusted to 80°C. The mixture was then pulverized into powder or small particles using a pulverizer to obtain the thermosetting compositions of Examples 1 to 6 and the thermoplastic compositions of Comparative Examples 1 and 2 (hereinafter, these may be collectively referred to as "compositions"). Crystalline radical polymerizable compound: urethane methacrylate (2-hydroxyethyl methacrylate adduct of 1,6-hexamethylene diisocyanate (2-HEMA adduct of 1,6-HDI)) Crystalline radical polymerizable compound: Ethoxylated isocyanuric acid triacrylate (A-9300, manufactured by Shin-Nakamura Chemical Co., Ltd.) Amorphous radical polymerizable compound: Epoxy (meth)acrylate (methacrylic acid adduct of bisphenol A type epoxy resin) Radical polymerizable monomer: Liquid methacrylate (methyl methacrylate) Epoxy resin: Bisphenol A epoxy resin (bisphenol A type epoxy methacrylate) Thermoplastic resin: Polyester resin (GM-960 manufactured by Toyobo Co., Ltd.) Inorganic filler: fused silica (manufactured by Denka Co., Ltd., average particle size: 24 μm) Silane coupling agent: Methacrylic silane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) Curing accelerator: Imidazole-adduct type latent curing agent (PN-50 manufactured by Ajinomoto Fine-Techno Co., Ltd.) Radical generator: Dicumyl peroxide (Percumyl D, manufactured by NOF Corp.) Radical scavenger: Parabenzoquinone (PBQ, manufactured by Seiko Chemical Co., Ltd.)
[0069] <Method of measuring endothermic start temperature TA1, endothermic end temperature TA2, and radical generation temperature TB1> Using a differential scanning calorimeter (DSC220) manufactured by Seiko Instruments Inc., 10 mg of each of the compositions was placed in an aluminum pan, the lid was pressed down to seal, and DSC measurements were performed at a temperature rise rate of 10°C / min from -60°C to 200°C. The start temperature of the endothermic peak of the obtained DSC curve was designated as TA1, the end temperature of the endothermic peak was designated as TA2, and the start temperature of the exothermic peak was designated as the radical generation temperature TB1. Note that the measurements were discontinued for the compositions of Examples 5 and 6, which were liquid at 23°C.
[0070] <Fluidity (melt viscosity)> As an index of the fluidity of the composition when heated, the melt viscosity was measured using a high-speed flow tester (CFT-500D) manufactured by Shimadzu Corporation. In detail, the composition was placed in a sample insertion hole of a cylinder equipped with a die having a diameter of 2.0 mm and a length of 10 mm and heated to 90°C, and after preheating for 180 seconds, the composition was measured for a melt viscosity of 3 to 100 kgf / cm. 2 The piston was pressed with a pressure of 0.01 to 0.15, and the composition was caused to flow out of the nozzle of the die at a shear rate of 1000 sec -1 The melt viscosity was determined from the point where the melt viscosity became 0.001, and the fluidity was evaluated according to the following criteria. A: Melt viscosity is 1000 Pa s or less B: Melt viscosity is over 1000 Pa s
[0071] <Glass transition temperature> The glass transition point of the composition was measured based on JIS K 7244-4. First, the composition was placed in a plate mold adjusted to 165°C, and the mold was closed to perform pressurized heat molding. The mold was then opened to obtain a plate-shaped test piece. The plate-shaped test piece was cut into a strip to obtain a test piece for measuring the glass transition point. Using an elasticity measuring device (DVA-220) manufactured by IT Measurement and Control Co., Ltd., dynamic viscoelasticity was measured at a temperature rise rate of 2°C / min, in the range of 30 to 250°C, and at a frequency of 10 Hz. The Tan δ peak temperature was taken as the glass transition point.
[0072] <Retention stability> The initial viscosity of the composition at 25°C and the melt viscosity after heating at 90°C for 24 hours were measured, and the rate of change was calculated to evaluate the residence stability according to the following criteria. The melt viscosity was measured by the method described above. A: Change rate less than 5% B: Change rate is 5% or more but less than 10% C: Change rate is 10% or more
[0073] <Blocking resistance> 200 g of the above composition was placed in a cylinder with a diameter of 75 mm and a height of 100 mm in an environment of 40°C, and a cylindrical weight of 74 mm in diameter and weighing 4 kg was placed from the top. After 24 hours had passed under the load, the composition was removed from the cylinder and the state of blocking between small particles in the composition was evaluated. A: No blocking between small particles B: There is blocking between small particles, but they do not fuse and dissolve. C: Small particles are blocked together and fused together, and cannot be separated.
[0074] <Curability> A hole of 30 mm in diameter was opened in the center of a Teflon (registered trademark) plate of 50 mm x 50 mm with a thickness of 2 mm to obtain a Teflon (registered trademark) sheet. The Teflon (registered trademark) sheet was then set in a heat press machine previously heated to 165 ° C., and the Teflon (registered trademark) sheet was heated to 165 ° C. Then, 3 g of the thermosetting composition of Example 1 was placed in the hole of the Teflon (registered trademark) sheet, and the sheet was heated for 3 minutes with a pressure of 5 MPa applied by the heat press machine to prepare a sample with a diameter of 30 mm and a thickness of 2 mm. Similarly, a sample heated for 5 minutes was also prepared. Each of these samples was subjected to DSC measurement at a temperature rise rate of 10 ° C. / min from -60 ° C. to 200 ° C. to confirm the presence or absence of an exothermic peak. Similarly, a sample heated for 3 minutes and a sample heated for 5 minutes were prepared for each of Examples 2 to 6, and DSC measurement was performed to confirm the presence or absence of an exothermic peak. In these DSC measurements, samples in which no exothermic peak was observed in the 3-minute sample and the 5-minute sample were determined to have a curing time of 3 minutes or less. Furthermore, if an exothermic peak was observed in the 3-minute sample but not in the 5-minute heated sample, the curing time was judged to be more than 3 minutes but not more than 5 minutes. If an exothermic peak was observed in both the 3-minute heated sample and the 5-minute heated sample, the curing time was judged to be more than 5 minutes. Curability was evaluated based on these criteria. A: Less than 3 minutes B: More than 3 minutes but less than 5 minutes C: More than 5 minutes
[0075] <Heat resistance> The weight change rate of the composition after heating at 200°C for 1 hour relative to the weight of the composition at 25°C before heating was measured to evaluate heat resistance. The weight change is presumed to be due to the amount of outgassing and the amount of volatilization of uncured components. The results are shown in Table 1. A: Weight loss rate is less than 0.3% B: Weight loss rate is 0.3% or more and less than 0.5% C: Change rate is 0.5% or more
[0076] [Table 1]
[0077] <Production of hardened solid> A 1.6 mm thick glass epoxy substrate (FR-4) without resist manufactured by Nikkan Kogyo was cut to a size of 40 mm x 40 mm, and the surface was wiped with acetone to remove oil. Then, the glass epoxy substrate 1 was inserted into a polybutylene terephthalate container 2 having a planar shape shown in Fig. 2 and a height of 50 mm with a cross-sectional shape of the X-X cross section of Fig. 2 shown in Fig. 3, and then inserted and fixed into a mold 5 having an upper mold 5a and a lower mold 5b and an inner dimension of 40 mm wide x 42 mm long x 50 mm high. Next, using a vertical low-pressure extrusion molding machine (IMC-18F9) manufactured by Imoto Seisakusho, which is a screw-type hot melt molding applicator, the compositions of Examples 1 to 6 were injected from a circular single gate with a diameter of 4 mm at the center of the upper surface of the upper mold 5a to perform molding. The molding conditions were a mold temperature of 25°C, a molding resin temperature of 80°C, a molding pressure of 3MPa, a holding pressure of 3MPa, and a discharge rotation of 50% (maximum discharge 100%). Then, the mold was released from the mold 5 to obtain a composite (solid composite 11) of the solid 10, the glass epoxy substrate 1, and the polybutylene terephthalate container 2 shown in FIG. 4. The solid composite 11 was further heated in a 165°C heating furnace for 3 minutes in Examples 1 to 4, 120 minutes in Example 5, and 3.5 minutes in Example 6 to obtain a cured solid composite. In addition, the width dimensions of the symbols a to h in FIGS. 2 and 3 are a=1.6mm, b=40mm, c=40mm, d=38mm, e=1mm, f=18.2mm, g=1mm, and h=9mm.
[0078] A 1.6 mm thick glass epoxy substrate (FR-4) without resist manufactured by Nikkan Industries was cut to a size of 40 mm x 70 mm, and the surface was wiped with acetone to remove oil. Then, a glass epoxy substrate 1 was placed inside a polybutylene terephthalate container 3 having a planar shape shown in FIG. 5 and a 50 mm high cross-sectional shape of the X-X cross section of FIG. 5 shown in FIG. 7. Furthermore, a polybutylene terephthalate frame 4 having a planar shape shown in FIG. 6 and a 10 mm high cross-sectional shape of the X-X cross section of FIG. 6 shown in FIG. 7 was placed inside the polybutylene terephthalate container 3. This assembly was inserted and fixed inside a mold 5 having an upper mold 5a and a lower mold 5b as shown in FIG. 7. Then, the compositions of Examples 1 to 6 were injected from a circular gate having a diameter of 4 mm provided at the center of the 18.2 mm x 38 mm surface of the upper mold 5a, in the same manner as the solid matter 10, to perform molding. Next, the mold 5 was released to obtain a composite (solid composite 21) of the solid 20, the glass epoxy substrate 1, the polybutylene terephthalate container 3, and the polybutylene terephthalate frame 4 shown in FIG. 8. The solid composite 21 was further heat-treated in a 165°C heating furnace for 3 minutes in Examples 1 to 4, 120 minutes in Example 5, and 3.5 minutes in Example 6 to obtain a hardened solid composite. In FIGS. 5 to 7, the width dimensions of symbols i to O are i=40 mm, j=38 mm, k=1 mm, l=1 mm, m=49 mm, n=10 mm, and O=10 mm. The width dimensions of symbols a, b, d, e, f, and h are as described above.
[0079] The solids 10 and 20 obtained from the compositions of Examples 1 to 6 had low melt viscosity during molding, and therefore were considered to have shapes conforming to the internal shapes of the polybutylene terephthalate container 2, polybutylene terephthalate container 3, and polybutylene terephthalate frame 4, respectively, and also to have shapes conforming to the shape of the glass epoxy substrate 1. Furthermore, it is considered that the hardened solids obtained after hardening treatment of these also had shapes conforming to the internal shapes of the polybutylene terephthalate container 2, polybutylene terephthalate container 3, and polybutylene terephthalate frame 4, and also to have shapes conforming to the shape of the glass epoxy substrate 1. The polybutylene terephthalate container 2, polybutylene terephthalate container 3, and polybutylene terephthalate frame 4 correspond to the above-mentioned "mold," and the glass epoxy substrate 1 corresponds to "other members" that are members other than the above-mentioned mold. [Explanation of symbols]
[0080] 1 Glass epoxy board 2. Polybutylene terephthalate container 3 Polybutylene terephthalate containers 4 Polybutylene terephthalate frame 5. Mold 5a Upper mold 5b Lower mold 10 Solids 11 Solid Complexes 20 Solids 21 Solid Complexes
Claims
1. A method for producing a solid of a thermosetting composition, comprising the steps of: A first heating step of heating at a temperature equal to or higher than the melting initiation temperature (° C.) of the thermosetting composition and lower than the curing initiation temperature (° C.) of the thermosetting composition; and A method for producing a solid product, comprising: a first cooling step of introducing the thermosetting composition into a mold by pouring, dropping or injecting the composition into the mold, and cooling the composition to a temperature below the melting initiation temperature (°C).
2. The method for producing a solid product according to claim 1 , wherein the thermosetting composition contains a crystalline radically polymerizable compound.
3. The method for producing a solid product according to claim 2 , wherein the thermosetting composition contains a radical generator that generates radicals at a temperature equal to or higher than the curing initiation temperature (° C.).
4. The method for producing a solid product according to any one of claims 1 to 3, wherein the melting initiation temperature is an endothermic initiation temperature TA1 (°C) in differential scanning calorimetry of the thermosetting composition.
5. The method for producing a solid material according to claim 4, wherein the endothermic onset temperature TA1 (°C) is 36°C or higher.
6. 6. The method for producing a solid product according to claim 1, wherein the curing initiation temperature is a temperature equal to or higher than an endothermic completion temperature TA2 (° C.)+10° C. in differential scanning calorimetry of the thermosetting composition.
7. A second heating step of heating the solid material at a temperature equal to or higher than the curing initiation temperature (° C.); and The method for producing a solid material according to any one of claims 1 to 6, further comprising a second cooling step of cooling the solid material to a temperature lower than the curing initiation temperature (°C).
8. The method for producing a solid material according to claim 7 , wherein the heating in the second heating step is performed collectively on the plurality of solid materials after the first cooling step.
9. The method for producing a solid material according to claim 7 , wherein the heating in the second heating step is performed by sequentially heating the plurality of solid materials after the first cooling step.
10. The method for producing a solid product according to any one of claims 1 to 9, wherein the thermosetting composition contains a radical scavenger.
11. The method for producing a solid product according to any one of claims 1 to 10, wherein the thermosetting composition contains a non-crystalline radically polymerizable compound.
12. The method for producing a solid product according to any one of claims 1 to 11, wherein the crystalline radical polymerizable compound is at least one selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and unsaturated polyester.
13. The method for producing a solid material according to any one of claims 1 to 12, wherein the solid material is used by being attached to an electric part.
Citation Information
Patent Citations
Crystalline radical-polymerizable composition for electric / electronic component, molded electric / electronic component obtained using said composition, and production method for said molded electric / electronic component
WO2018159387A1
Preform production method and preform production device
WO2019188417A1
Method for manufacturing molded article, and method for manufacturing electronic component device
WO2019189464A1